YPI SYAHDA BOYOLALI MENUJU PESANTREN MANDIRI DI ERA DIGITAL MELALUI PENERAPAN AGRIBISNIS TERPADU, PENGEMBANGAN JIWA WIRAUSAHA DAN PEMASARAN BERBASIS E-COMMERCE - Setiawati, Donna; Wahyono, Ari; Pratiwi, Yunita Niqrisah Dwi; Wulandari, Eudia Christina; Muryanto, Sigit; Wicaksono, Enggar Alif; Waryanti, Nia (Jurnal Abdi Insani, 2024)
The Islamic Boarding School (Ponpes) Yayasan Pendidikan Islam (YPI) Syahda is located in Dk. Randu RT 08 RW 02 Ds. Temon, Kec. Simo, Kab. Boyolali, currently has 102 students, but 21 students live in the boarding school. The educational model of the partner Islamic boarding school is traditional in the form of sorogan and bandongan methods, and students receive useful soft skills support such as information technology education with graphic design materials. However, the output of the current soft skills products has not provided a significant income generating impact for students. The purpose of implementing the activity is to improve soft skills and hard skills in the field of Entrepreneurship for the development of an entrepreneurial spirit, increase production capacity in implementing an integrated agricultural system that is integrated to maximize agricultural, livestock and fishery products and expand marketing through e-commerce-based digital marketing. The method of implementing activities with structured, systematic and well-planned work procedures through 5 stages of implementing community service. The results of this activity are that students have an entrepreneurial spirit so that they will be able to process the potential owned by the boarding school by implementing an integrated agricultural system whose agricultural products can be marketed through online marketing.